Thicker than water : - Davidoff, Leonore (Oxford University Press, 2012)
Leonore Davidoff is a Research Professor in the Department of Sociology at the University of Essex. She has held visiting professorships and fellowships in the US, Australia, Sweden, and several other European countries. Her main area of research is the relationship between the family and economic organization in the period of nascent capitalist development from around 1780 to 1920. She has also pioneered the history of gender relations and in 1987 she became Founding Editor of Gender and History.